Report of the special conference on trade union and collective bargaining rights of public employees held at Munich, October 1953 (International Federation of Unions of Employees in Public and Civil Services)
With: Neumeyer, P., Trade union rights and activities of employees in public services. Hayday, F., Negotiating machinery in the public services. Oesterle, K., Codetermination. Stencil.